Implementasi Supervisi Akademik Dalam Meningkatkan Profesionalisme Guru di Madrasah Aliyah Nurul Jadid - Rifa’i, Moh; Amanah, Sidqiyah (UMSU, 2024)
The low level of education in Indonesia can be caused by the low level of educational human resources in Indonesia, namely educators or teachers who do not have professionalism in carrying out their duties. Academic supervision is one way that can be taken to improve the quality of education through career development or professionalism of a teacher. Academic supervision leads to improving educational problems by guiding, supervising, mentoring and directing teachers to become professional in their field to improve education and fix problems in education. Academic supervision helps teachers make plans in the learning process so as to produce the desired output in learning. The aim of writing this article is to examine academic supervision in increasing teacher professionalism. This type of article writing method uses a qualitative method with descriptive analysis. Based on research studies, several results were obtained that academic supervision consists of two parts, namely individual supervision and group supervision.